DIFFERENT APPROACHES TO THE DEFINITION OF THE CONCEPT "READY FOR SELF-REALIZATION" IN PROFESSIONAL ACTIVITY - N.V. Ponomarenko (Academy of Cognitive and Natural Sciences, 2007)
The different ways to the determination to the definition of "readiness for self-actualization" in professional occupation is examined in this article. There was the attempt to give the determination to this definition.